The Urgency of Regulating Written Statement Format as an Administrative Requirement for Organ and Tissue Transplants - Anandita, Azzavira Salsa; Djumikasih Djumikasih; Rino Arief Rachman (CV. AFDIFAL MAJU BERKAH, 2025)
This study discusses the administrative requirements for organ and tissue transplantation in Indonesia, particularly the form of the “written statement” which has not been fully accommodated in the current health legislation. There is a discrepancy between administrative requirements in Government Regulation No. 28 of 2024 and Ministry of Health Regulation No. 38 of 2016. Therefore, a normative ambiguity arises, which the author addresses through this research questions: (1) What is the urgency of regulating the form of a 'written statement' as an administrative requirement for organ and human tissue transplantation in Indonesia? and (2) What is the appropriate form of the “written statement” as an administrative requirement for transplantation? To answer these questions, the author uses normative juridical research methods and applies three approaches: statutory, conceptual, and comparative. The analysis is conducted through grammatical and systematic interpretation. The study finds that the regulation of the written statement is still unclear, causing legal uncertainty. Yet, such a document is crucial for ensuring that the transplantation process is legal, voluntary, and transparent, and to prevent organ trafficking. Therefore, a more specific regulation is needed. The study concludes that notarial deed is the most appropriate form to express the donor’s consent legally, ethically, and responsibly.